The Stability of Retrospective Pre-injury Symptom Ratings Following Pediatric Concussion - Teel, Elizabeth F.; Zemek, Roger L.; Tang, Kenneth; Gioia, Gerard; Vaughan, Christopher; Sady, Maegan; Gagnon, Isabelle J.; , the Pediatric Emergency Research Canada (PERC) Concussion Team; Osmond, Martin H.; Barrowman, Nick; Freedman, Stephen B.; Gravel, Jocelyn; et al. (Frontiers in Neurology, 2019)
Objective: To determine the stability of children's retrospective ratings of pre-injury levels of symptoms over time following concussion. Methods: Children and adolescents (n = 3,063) between the ages of 5–17 diagnosed with a concussion by their treating pediatric emergency department (PED) physician within 48 h of injury completed the Post-Concussion Symptom Inventory (PCSI) at the PED and at 1, 2, 4, 8, and 12-weeks post-injury. At each time point, participants retrospectively recalled their pre-injury levels of post-injury symptoms. The PCSI has three age-appropriate versions for children aged 5–7 (PCSI-SR5), 8–12 (PCSI-SR8), and 13–18 (PCSI-SR13). Total scale, subscales (physical, cognitive, emotional, and sleep), and individual items from the PCSI were analyzed for stability using Gini's mean difference (GMD). Results: The mean GMD for total score was 0.31 (95% CI = 0.28, 0.34) for the PCSI-SR5, 0.19 (95% CI = 0.18, 0.20) for the PCSI-SR8, and 0.17 (95% CI = 0.16, 0.18) for the PCSI-SR13. Subscales ranged from mean GMD 0.18 (physical) to 0.31 (emotional) for the PCSI-SR8 and 0.16 (physical) to 0.31 (fatigue) for the PCSI-SR13. At the item-level, mean GMD ranged from 0.13 to 0.60 on the PCSI-SR5, 0.08 to 0.59 on the PCSI-SR8, and 0.11 to 0.41 on the PCSI-SR13. Conclusions: Children and adolescents recall their retrospective pre-injury symptom ratings with good-to-perfect stability over the first 3-months following their concussion. Although some individual items underperformed, variability was reduced as items were combined at the subscale and full-scale level. There is limited benefit gained from collecting multiple pre-injury symptom queries. Clinical Trial Registration: Clinicaltrials.gov through the US National Institute of Health/National Library of Medicine. (NCT01873287; http://clinicaltrials.gov/ct2/show/NCT01873287).